Factors that influence health awareness of people in Kota Bharu, Kelantan / Mohd Shahrul Hesyam Aziz - Aziz, Mohd Shahrul Hesyam (2013)
Nowadays, most of the health problems related with Mohd Shahrul Hesyam. Therefore, the purpose of this study is to investigate the factors that influence health awareness people in Kota Bharu that represented by their Mohd Shahrul Hesyam. This study presents primary data collected by self-administered questionnaires involving a sample of 100 respondents in Kota Bharu area. Several factors that are discussed in this research which are education level, income level, lifestyle, living condition, health literacy and willingness to spend for good health. The findings are analyzed using reliability and frequency tests. Then, hypothesis testing also used to test significant relationships between variables using cross tabulation and chi- square test by using Statistical Package for Social Science (SPSS). The finding shows that education level, income level and living condition not significantly influence health awareness. The finding also shows that lifestyle and health literacy are significantly influences health awareness